2023
DOI: 10.1177/20503121231197869
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and COVID-19 vaccine acceptance worldwide: A systematic review

Eneyew Talie Fenta,
Misganaw Guadie Tiruneh,
Amare Mebrate Delie
et al.

Abstract: Objective: Health literacy helps an individual to have the capacity to obtain, process, and understand basic health information to make appropriate health decisions. This study aimed to review the association between health literacy and COVID-19 vaccine acceptance. Method: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses steps. Databases including PubMed/MEDLINE, Web of Science, Scopus, EMBASE, World Health Organization libraries, and Google Scholar were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…These findings were contradicted by other investigations published during the same period [28,31]. Notably, these proportions are similar to those of our previous review [16], and of two systematic reviews, where 10 out of 13 papers reported a positive association between VL and COVID-19 vaccine acceptance [15], and 18 out of 21 showed an association between VL and acceptance, positive attitudes, or beliefs toward different vaccines [6].…”
Section: Step 3: Theoretical Frameworkcontrasting
confidence: 47%
See 2 more Smart Citations
“…These findings were contradicted by other investigations published during the same period [28,31]. Notably, these proportions are similar to those of our previous review [16], and of two systematic reviews, where 10 out of 13 papers reported a positive association between VL and COVID-19 vaccine acceptance [15], and 18 out of 21 showed an association between VL and acceptance, positive attitudes, or beliefs toward different vaccines [6].…”
Section: Step 3: Theoretical Frameworkcontrasting
confidence: 47%
“…At the time when this paper was drafted, a meta-analysis has been published on the relationship on VLs, and vaccine intention, acceptance, or uptake, conducted on 18 studies, most of which already reported in previous reviews [14]. The results confirmed that VL significantly predicts vaccination intention, although its correlation with vaccination status (vaccine uptake) was comparatively weaker, despite being evidenced in several publications [6,15,16]. Notably, these results fit the proposed framework, as they highlight the position of VL between antecedents (moderators) and mediating variables, suggesting its indirect, and/or direct effect on behaviors and outcomes.…”
Section: Step 3: Theoretical Frameworkmentioning
confidence: 60%
See 1 more Smart Citation
“…According to a recent systematic review [39], the low acceptance of the vaccine has been associated with low levels of education and awareness and inefcient governmental efforts and initiatives. For this reason, investing in health literacy improves the acceptance of the vaccine and the making of health-related decisions, to reduce the impact of the COVID-19 pandemic [40]. On the other hand, the most prevalent secondary efect was alterations to the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Work on the vaccination of children during and before COVID-19 showed a link between health literacy and the likelihood of childhood vaccination. [29][30][31] Hence, it is important to provide caregivers with accurate information for future vaccines and to increase levels of trust in the health establishment.…”
Section: Discussionmentioning
confidence: 99%